2022
DOI: 10.3390/ijerph19127195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Infant Injury Prevention Education Provided during Antenatal Classes after Two Years: A Pilot Prospective Cohort Study

Abstract: This study examined the long-term effects of an infant injury prevention program implemented during an antenatal class of 131 mothers. Questionnaires were completed 2 years postpartum to assess the incidence of injury (medically attended or home-care), mothers’ perception of injury prevention, implementation of safety practices, and active attitudes toward injury prevention. Responses were obtained from 68 (51.9%) mothers (intervention group, 40; control group, 28), including 24 who reported medically attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Finally, providing practical experience and feedback as a teaching method for safety accident prevention competency reinforcement is a notable factor in interventions for the prevention of safety accidents involving infants. Honda et al [ 34 ] reported that providing practical experience reinforces an active attitude toward injury prevention and safety behavior practices. There is a reported demand for education related to practical management methods among parents of infants and toddlers to reinforce the safety of their children at home [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, providing practical experience and feedback as a teaching method for safety accident prevention competency reinforcement is a notable factor in interventions for the prevention of safety accidents involving infants. Honda et al [ 34 ] reported that providing practical experience reinforces an active attitude toward injury prevention and safety behavior practices. There is a reported demand for education related to practical management methods among parents of infants and toddlers to reinforce the safety of their children at home [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Services, such as interviews when submitting pregnancy noti cation (pregnancy noti cation interview), prenatal education, postpartum home visits, and infant health examinations, are conducted by local governments and have high participation rates, providing ideal opportunities for the dissemination of injury prevention education about injuries that can occur to anyone at any time. As a result of the injury prevention education provided in the antenatal class, mothers who received this education were more likely to practice preventative behaviors postpartum and understand injury prevention awareness, severity, and probability of injury two years later (6) (7). Thus, educating caregivers promotes knowledge, awareness, and behavioral change.…”
Section: Introductionmentioning
confidence: 99%